Cross‐Platform DNA Encoding for Single‐Cell Imaging of Gene Expression. (7th June 2016) - Zrazhevskiy, Pavel; Akilesh, Shreeram; Tai, Wanyi; Queitsch, Konstantin; True, Lawrence D.; Fromm, Jonathan; Wu, David; Nelson, Peter; Stamatoyannopoulos, John A.; Gao, Xiaohu
Abstract: Integration of imaging data across different molecular target types can provide in‐depth insight into cell physiology and pathology, but remains challenging owing to poor compatibility between target‐type‐specific labeling methods. We show that cross‐platform imaging analysis can be readily achieved through DNA encoding of molecular targets, which translates the molecular identity of various target types into a uniform in situ array of ssDNA tags for subsequent labeling with complementary imaging probes. The concept was demonstrated through multiplexed imaging of mRNAs and their corresponding proteins with multicolor quantum dots. The results reveal heterogeneity of cell transfection with siRNA and outline disparity in RNA interference (RNAi) kinetics at the level of both the mRNA and the encoded protein.